N-Heterocyclic Carbenes Derived from Guanosine - Leitão, Maria Inês P.S. (2019)
Palladium(II) and platinum(II) complexes bearing N-heterocyclic carbenes derived from guanosine are synthesized via oxidative addition, followed by protonation in the presence of acid. Cytotoxicity of the compounds is evaluated in several cell lines. Compounds 2a, 2b, and 3a are selective for glioblastoma U251 cells and are nontoxic toward healthy human embryonic kidney (HEK293) cells.